The effect of Oxalis corniculata extract against the behavioral changes induced by 1-methyl- 4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) in mice - K. Aruna, P. Devi Raja Rajeswari, S. Raja Sankar (Journal of Applied Pharmaceutical Science, 2017)
Parkinson’s disease (PD) is a neurodegenerative disorder characterized by the development of rigidity, resting tremors and postural instability. Recently, the focus of PD’s treatment has shifted towards herbal medicines. The aim of the study was to evaluate neuroprotective effect of alcoholic extract of Oxalis corniculata (Oxalidaceae), via the analysis of behavioral features in MPTP (1-methyl,4- phenyl-1,2,3,6-tetra hydro pyridine) mouse model. Behavioral studies were performed by the actophotometer, elevated plus maze, rotarod, hole board, step down and step through tests. Treatment with O. corniculata reversed the alterations in locomotor and muscle coordination in MPTP induced Parkinsonic mouse. The results achieved in this study reveal that different doses of O. corniculata increased memory retention and retrieval significantly. Memory retention and retrieval enhancement by O. corniculata extract could be due to the presence of antioxidants such as flavonoids, coumarins, tocopherols and phenolic acids and their power in scavenge reactive oxygen species.
Keywords: Behaviour, MPTP, Oxalis corniculata, Parkinson’s disease.